Intricate lattice work on the windows - Mumbai Archive Project Team (Jio Institute, 2024)
The Aga Khan Maqbara features intricate lattice work on the windows of its central chamber. The structure is built primarily of sandstone, with white marble cladding used sparingly for ornamentation embellishments